A microwave powered polymeric artificial muscle. (June 2021) - Aziz, Shazed; Villacorta, Byron; Naficy, Sina; Salahuddin, Bidita; Gao, Shuai; Baigh, Tajwar A.; Sangian, Danial; Zhu, Zhonghua
Highlights: Electromagnetic energy triggered carbon nanotube mixed polymeric artificial muscles. Anisotropic thermal expansion of highly-drawn fibres through radiation heating. Fast actuation response though volumetric heating of irradiated carbon nanotubes. Artificial muscles for soft robotic devices to operate in microwave radiation zone. Abstract: Twisted and coiled polymer fibres are vastly used to fabricate artificial muscles with stroke and stress outputs rivalling those of mammalian muscles. The thermal stimulation of these fibres, however, requires a tethered power source, limiting their application as truly autonomous system. Here, a novel type of coiled polymer actuator is demonstrated where thermal stimulation is realized via microwave radiation. This helical writhe shaped actuator is made of carbon nanotube (CNT) filled highly-drawn nylon 6 fibres and offers muscle-like linear movements when microwave-irradiated. The embedded CNTs absorb the external electromagnetic energy and act as volumetric heating sources in the fibres. When stimulated via microwave radiation, the unique anisotropic thermal expansion phenomenon of highly-drawn fibres provides >8% reversible length contraction of the writhe muscle with a starting actuation speed of 0.8%/sec. The maximum specific work output is calculated to be 0.2 kJ/kg, which is >5 fold higher than that for natural muscle. The developed technology offers an opportunity to stimulate the state-of-art thermoresponsive artificial muscles wirelessly and/or to use them for autonomous soft robotic application. Graphical abstract: Image, graphical abstract